(untitled) (Development Service Industry Management, 2025)
This article substantiates the crucial role of a manager’s cross-cultural competence (CQ) as a strategically vital resource for enterprises operating within the context of increasing globalization. It conducts a thorough analysis of contemporary theoretical approaches to the concept of cultural intelligence, revealing a number of significant gaps that necessitate further research and practical solutions. Among the identified shortcomings, particular emphasis is placed on the absence of industry-specific metrics for assessing CQ, the limited availability of accessible and effective interactive learning platforms aimed at developing intercultural skills, and the insufficient integration of CQ assessment results into the overall performance management systems of personnel within enterprises. Special attention in the study is devoted to the Ukrainian context. The analysis is carried out taking into account the requirements of national standards DSTU ISO 10015:2011, which regulate the quality management of training, education, and development. The results of empirical studies conducted in Ukrainian enterprises are presented, clearly demonstrating the urgent need for the adaptation and localization of existing tools for assessing and developing cross-cultural competence, considering the specifics of the national business environment and cultural peculiarities. Within the framework of the research, an innovative three-level industry model of cross-cultural competence (CQ) is proposed. This model includes: the macro-level, encompassing legislative and regulatory requirements that influence intercultural interaction in business; the meso-level, reflecting established industry practices and norms of intercultural communication; and the micro-level, taking into account the specifics of the organizational culture of an individual enterprise and its impact on the manifestations of employees’ CQ. Furthermore, to ensure the rapid and effective diagnosis of the level of cultural intelligence, a shortened version of the existing CQS (Cross-Cultural Competence Scale) – CQS-Short – has been developed. This scale consists of only 12 carefully selected items, allowing for a quick assessment of the key components of CQ: motivational (interest and desire for intercultural interaction), cognitive (knowledge about cultural differences and the ability to interpret them), and behavioral (the ability to adapt one’s behavior in an intercultural context). The proposed scale serves as a practical tool for the rapid assessment and further development of the cross-cultural competence of managerial personnel.